Pengaruh Digital Marketing Dan Brand Awareness Terhadap Minat Beli Produk Subeng Klasik - Mareta Nurul Fitri; Siti Mabrur Rachmah (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The purpose of this study is to analyze the influence of digital marketing on consumer interest in buying " Subeng Klasik". " Subeng Klasik " is one type of traditional Indonesian jewelry, especially earrings (giwang) which are commonly used in Javanese, Balinese, and several other regions. This study is a descriptive quantitative study with a multiple linear regression analysis method. Respondents in this study were Instagram users who knew the Subeng Klasik product, totaling 100 respondents. Based on the results of data analysis, the results of this study are as follows; (1) Digital Marketing partially has a positive and significant effect on Purchase Interest of Subeng Klasik products; (2) Brand Awareness partially has a positive and significant effect on Purchase Interest of Subeng Klasik products. The coefficient value of Brand Awareness is greater than Digital Marketing, which indicates that Brand Awareness has a relatively greater influence on Purchase Interest than Digital Marketing; (3) Digital Marketing and Brand Awareness simultaneously or together have a positive and significant effect on Purchase Interest of Subeng Klasik products.